Effect on the uptake kinetics of serotonin (5-hydroxytryptamine) in platelets from workers with long-term exposure to organic solvents. A pilot study. - Beving, H.; Kristensson, J.; Malmgren, R.; Olsson, P.; Unge, G. (Scandinavian Journal of Work, Environment & Health, 1984)
Six workers from a paint industry were examined concerning the concentration of solvents in the breathing zone, the platelet count and kinetic uptake of serotonin [5-hydroxytryptamine (5-HT)], the serum concentration of calcium, potassium and sodium, and pH. The degree of exposure was found to be moderate. The results showed a decrease in platelet count in whole blood and platelet-rich plasma. The maximum uptake rate for serotonin in platelets (Vmax) was significantly increased compared to that of nonexposed subjects. No changes in the ionic concentration and pH of serum were observed. One worker was reexamined after a six-week period of nonexposure. Though the measured platelet variables were still aberrant, the values approached normal.